Workplace Retention Drivers in a Multigenerational Workforce: Analyzing Gen Y and Gen Z perspectives - Sehgal, Amit (Digital Repository of Theses - SSBM Geneva, 2025)
The growing influence of Generation Y (Millennials) and Generation Z in the Indian labor market is reshaping organizational structures, cultures, and talent management strategies. This study adopts a comparative quantitative research design to examine how four critical factors—workplace culture, career development, compensation and benefits, and work-life balance—affect retention intentions among Gen Y and Gen Z employees in Indian organizations. Grounded in established theories, the research surveyed over 400 professionals across key industries, ensuring methodological rigor and validity. Generational analyses reveal important differences. Gen Z employees are especially sensitive to workplace culture, value alignment, and flexible arrangements, all of which strongly influence their retention intentions. For this cohort, organizational ethics and purpose are not just ideals but essential criteria for employment decisions. Gen Y, while also valuing these factors, places relatively more emphasis on career development and compensation structure, aligning with their life stage and career trajectories. Compensation and benefits remain important for both groups but are perceived differently. Millennials seek financial stability, and comprehensive benefits, while Gen Z Favors equitable, transparent, and flexible compensation structures, including wellness rewards . Customizable benefit packages have a stronger retention effect for Gen Z, though both generations consider non-monetary recognition and opportunities for skill development highly influential. Work-life balance emerged as a critical retention factor, especially in the post-pandemic context. Millennials prefer hybrid work arrangements and flexibility, whereas Gen Z values digital integration, autonomy, and mental health support. The ability to harmonize personal and professional priorities directly influences retention and amplifies the impact of workplace culture and development opportunities. The study also finds that organizational commitment and perceived organizational support moderate retention intentions. While Millennials remain loyal under favourable commitment, Gen Z responds more to authentic leadership and responsiveness rather than traditional hierarchical loyalty. Study also finds that the generation-specific retention frameworks significantly lower turnover intention across cohorts and HR leaders should look at tailored HR strategies as an effective tool than universal approaches for engagement and retention. Addressing a gap in the Indian context, this thesis provides a nuanced model that considers cultural, economic, and technological factors. It concludes that aligning HR strategies with generational expectations—through authentic culture, agile career paths, equitable compensation, and holistic well-being—can significantly improve retention and foster a sustainable, future-ready workforce.